Honeybees and Animal Narratives (Overview of the (Un)Common Worlds Art Programme) - Vilma Mättö (Finnish Society for Human-Animal Studies, 2025)
Overview of the art programme seen during the (Un)Common Worlds conference (7.-9. 8. 2018, Turku.)